Cardiac and hepatic role of r‐AtHSP70: basal effects and protection against ischemic and sepsis conditions. Issue 7 (23rd April 2015) - Pasqua, Teresa; Filice, Elisabetta; Mazza, Rosa; Quintieri, Anna Maria; Carmela Cerra, Maria; Iannacone, Rina; Melfi, Donato; Indiveri, Cesare; Gattuso, Alfonsina; Angelone, Tommaso
Abstract Heat shock proteins (HSPs), highly conserved in all organisms, act as molecular chaperones activated by several stresses. The HSP70 class of stress‐induced proteins is the most studied subtype in cardiovascular and inflammatory disease. Because of the high similarity between plant and mammalian HSP70, the aim of this work was to evaluate whether recombinant HSP70 of plant origin (r‐AtHSP70) was able to protect rat cardiac and hepatic function under ischemic and sepsis conditions. We demonstrated for the first time that, in ex vivo isolated and perfused rat heart, exogenous r‐AtHSP70 exerted direct negative inotropic and lusitropic effects via Akt/endothelial nitric oxide synthase pathway, induced post‐conditioning cardioprotection via Reperfusion Injury Salvage Kinase and Survivor Activating Factor Enhancement pathways, and did not cause hepatic damage. In vivo administration of r‐AtHSP70 protected both heart and liver against lipopolysaccharide‐dependent sepsis, as revealed by the reduced plasma levels of interleukin‐1β, tumour necrosis factor alpha, aspartate aminotransferase and alanine aminotransferase. These results suggest exogenous r‐AtHSP70 as a molecular modulator able to protect myocardial function and to prevent cardiac and liver dysfunctions during inflammatory conditions.